Applying value at risk and riskiness models to analyze the flood loss of transportation construction projects in Taiwan. (3rd April 2021) - Chen, Po-Han; Peng, Tsu-Te; Chen, Chieh-Jan
ABSTRACT: Because of Taiwan's specific geographical location, disastrous weather phenomena such as typhoons, extreme rainfall, flooding, and regional flooding occur frequently, resulting in devastating casualties and property loss. The losses caused by flooding are NT$5.5 billion per year. This study used insurance claims data on flood damage in Taiwan's transportation construction projects (from 1996 to 2007) as a sample space. Statistical actuarial model analysis was performed to normalize the loss factors, thereby enabling loss model testing and quantitative analysis of the normalized loss factors. To evaluate the risk in transportation construction, two models were separately applied in the analysis: the value at risk and riskiness models. The results may aid in estimating flooding damage losses in transportation construction projects.